Frequency of the TREM2 R47H Variant in Various Neurodegenerative Disorders. (October 2019) - Ayer, Ariane H.; Wojta, Kevin; Ramos, Eliana Marisa; Dokuru, Deepika; Chen, Jason A.; Karydas, Anna M.; Papatriantafyllou, John D.; Agiomyrgiannakis, Dimitrios; Kamtsadeli, Vasiliki; Tsinia, Niki; Sali, Dimitra; Gylys, Karen H.; et al.
Abstract : Objective: A rare variant in TREM2 (p.R47H, rs75932628) has been consistently reported to increase the risk for Alzheimer disease (AD), while mixed evidence has been reported for association of the variant with other neurodegenerative diseases. Here, we investigated the frequency of the R47H variant in a diverse and well-characterized multicenter neurodegenerative disease cohort. Methods: We examined the frequency of the R47H variant in a diverse neurodegenerative disease cohort, including a total of 3058 patients clinically diagnosed with AD, frontotemporal dementia spectrum syndromes, mild cognitive impairment, progressive supranuclear palsy syndrome, corticobasal syndrome, or amyotrophic lateral sclerosis and 5089 control subjects. Results: We observed a significant association between the R47H variant and AD, while no association was observed with any other neurodegenerative disease included in this study. Conclusions: Our results support the consensus that the R47H variant is significantly associated with AD. However, we did not find evidence for association of the R47H variant with other neurodegenerative diseases. Abstract : Supplemental Digital Content is available in the text.